Downregulation of LHCGR Attenuates COX-2 Expression and Induces Luteinized Unruptured Follicle Syndrome in Endometriosis - Geng, Ting; Sun, Yifan; Cheng, Lin; Cao, Yuming; Zhang, Ming; Hong, Zhidan; Ma, Ling; Zhang, Yuanzhen (Frontiers in Endocrinology, 2022)
An association between endometriosis and luteinized unruptured follicle syndrome (LUFs) has long been identified. Although inactivating mutation of luteinizing hormone/choriogonadotropin receptor (LHGCR) results in LUFs, whether LHCGR contributes to promoting LUFs in endometriosis remains elusive. To investigate the effect of LHCGR signaling in the development of endometriosis-associated LUFs and dissect the underlying mechanism in vivo mouse endometriosis model was established to measure the effect on ovarian folliculogenesis. In vitro cultures of primary human GCs collected from patients undergoing in vitro fertilization were performed and treated with human chorionic gonadotropin (hCG), dibutyryl cyclic-AMP (db-cAMP), LHCGR or CCAAT/enhancer binding protein-α (C/EBPα) small interfering RNA to identify the potential mechanisms. KGN cell line was used to investigate the mechanistic features of transcriptional regulation. Results showed an increased incidence of LUFs was observed in mice with endometriosis. The expression of LHCGR was decreased in the GCs of endometriosis mice. In in vitro cell models, LHCGR signaling increased the expression of C/EBPα and cyclooxygenase-2(COX-2), while inhibiting C/EBPα mitigated the induced COX-2 expression. Mechanically, C/EBPα bounded to the promoter region of COX-2 and increased the transcriptional activity under the stimulation of hCG or db-cAMP. Taken together, this study demonstrated that the LHCGR signaling was reduced in GCs of endometriosis and resulted in a decrease in gonadotropin-induced COX-2 expression. Our study might provide new insights into the dysfunction of GCs in endometriosis.